Nutritional Status of Women in Narayanpur Block, Mirzapur District, U.P. - Singh, Shikha; Singh, M. B. (National Geographical Journal of India, 2022)
Nutrition ‘is an important factor to determine individual’s health. In this study some indicators such as food consumption, height and weight of women are adopted for analysing nutritional status. On the basis of height and weight the body mass index has been assessed. Present study also analyses the effect of education, income, age, nature of job and family type of women on their nutritional status. The condition of undernutrition is more frequent among Muslim women followed by SC women.The mean height in the study (155cm) area is higher than the average of Uttar Pradesh and India.